2015
DOI: 10.1021/acsami.5b07325
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dimethylsiloxane)-Based Polyurethane with Chemically Attached Antifoulants for Durable Marine Antibiofouling

Abstract: Marine biofouling is a problem for marine industry and maritime activities. We have prepared polyurethane with poly(dimethylsiloxane) (PDMS) main chains and N-(2,4,6-trichlorophenyl) maleimide (TCM) pendant groups via a combination of a thiol-ene click reaction and a condensation reaction and studied its properties. The polymer has low surface energy and a high water contact angle. When TCM content in bulk is high enough, sufficient antifoulant groups can be exposed on the surface. Our study reveals that such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…The biodegradation of PDMS based on the cleavage of SiC bonds is too slow to be observed under the test conditions at room temperature . It has been shown that un‐crosslinked linear PDMS chains resist biofouling and for up to a month in sea water and biodegrading slowly starts to occur after 110 d . On the other hand, PDMS can be decomposed in soil/sludge depending on molecular weight and structure as well as the moisture and microorganism contents of soil .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biodegradation of PDMS based on the cleavage of SiC bonds is too slow to be observed under the test conditions at room temperature . It has been shown that un‐crosslinked linear PDMS chains resist biofouling and for up to a month in sea water and biodegrading slowly starts to occur after 110 d . On the other hand, PDMS can be decomposed in soil/sludge depending on molecular weight and structure as well as the moisture and microorganism contents of soil .…”
Section: Resultsmentioning
confidence: 99%
“…PDMS is a well‐known nontoxic, biocompatible polymer and is safe for the environment . It was reported that cross‐linked PDMS exhibits minimal biodegradation under sea water due to low surface energy and inherent hydrophobicity leading to weak interactions with organisms in sea water . The biodegradation of PDMS based on the cleavage of SiC bonds is too slow to be observed under the test conditions at room temperature .…”
Section: Resultsmentioning
confidence: 99%
“…The latter strategies are based on various alternatives of supramolecular chemistry, self‐assembly, phase‐separation of polymers, and chemical building blocks for the creation of coatings with tunable nanoscale surface properties. Lately, a range of approaches has been investigated that span from bioinspired polymers incorporating bioactive molecules and enzymes to hydrophobic or hydrophilic self‐assembling monolayers, hydrophobic fluoropolymer networks, antimicrobial quaternary ammonium polymers, self‐stratifying polysiloxane hybrids, poly(2‐methyl‐2‐oxazoline)s and polyethylene glycol hydrogels, xerogels, zwitterionic polymers, layer‐by‐layer assemblies, nanocomposites containing nanofillers of varying nanoscale dimensions and photocatalytic nanoparticles, to self‐polishing silyl ester polymers …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that the materials having surface energy 23–25 mJ/m has the lowest interfacial tension with biological macromolecules and gives the minimum driving force for adsorption. It is further known that the surface energy of 23–25 mJ/m ensures the lowest possible bonding strength of fouling organisms …”
Section: Resultsmentioning
confidence: 99%